Review of species of the Astyanax bimaculatus “caudal peduncle spot” subgroup sensu Garutti & Langeani (Characiformes, Characidae) from the rio La Plata and rio São Francisco drainages and coastal systems of southern Brazil and Uruguay - Lucena, Carlos Alberto S. De; Soares, Helena Gouvea (Zootaxa, 2016)
The species of the Astyanax bimaculatus ’caudal peduncle spot’ subgroup of the drainages of the rios La Plata and São Francisco, as well as southeastern coastal systems of Brazil and Uruguay, are revised. Two nominal species are considered valid and are redescribed: Astyanax lacustris and A. abramis. Astyanax jacuhiensis, A. asuncionensis and A. altiparanae are recognized as new junior synonyms of A. lacustris. Bertoniolus paraguayensisis recognized as a new junior synonym of A. abramis. The names Astyanax orbignyanus, A. vittatus, and A. borealis are considered species inquirendae. Notes on A. maculisquamis, included in the ’caudal peduncle spot’ subgroup from rio Guaporé (rio Madeira drainage), and Astyanax bahiensis from Bahia, mistakenly considered of the same subgroup, are presented.